Evaluation of the Viability of Implementation of Renewable Hybrid Systems for Energy Access in the Amazon Region (Research, Society and Development, 2019)
The Amazon Region is characterized by having a dense and heterogeneous forest, large and extensive rivers, which the access to electricity is difficult, for this reason, is insered in the Isolated System (SI). The SI is composed by smaller systems not connected to the National Interconnected System (SIN), which the costs of interconnections are not feasible. In the current scenario, renewable energy sources are attracting a large number of researchers due to the growing scarcity of fossil fuels. One of the alternatives that have been studied to facilitate the supply of energy in these localities is the use of hybrid renewable energy systems (SH). Thus, the present study aims to evaluate the potential of renewable SH in the Amazon Region. For this, a comparative table of the types of renewable energy with potential use in SH and a SWOT Matrix was elaborated through a bibliographic review. From the analysis developed, it was noticed that there are a significant number of positive points that combined with governmental incentive policies of tax and credit can make feasible the implementation of hybrids of renewable energy.